In vivo and in vitro effect of capsicum annum proteinase inhibitors on helicoverpa armigera gut proteinases - Tamhane, V. A.; Chougule, Nanasaheb P.; Giri, Ashok P.; Dixit, A. R.; Sainani, Mohini N.; Gupta, Vidya S. (Biochimica Et Biophysica Acta-General Subjects, 2005)
Two proteinase inhibitors (PIs), CapA1 and CapA2, were purified from Capsicum annum Linn. Var. Phule Jyoti leaves and assessed for their in vitro and in vivo activity against Helicoverpa armigera gut proteinases (HGPs). Both the inhibitors exhibited molecular weights of about 12 kDa with inhibitory activity against bovine trypsin and chymotrypsin indicating presence of probable two-inhibitor repeats of PIN II family. CapA1 and CapA2 inhibited 60-80% HGP (azocaseinolytic) activity of fourth instar larvae feeding on various host plants while 45-65% inhibition of HGP activity of various instars (II to VI) larvae reared on artificial diet. The partial purification of HGP isoforms, their characterization with synthetic inhibitors and inhibition by C. annum PIs revealed that most of the trypsin-like activity (68-91%) of HGPs was sensitive to C. annum PIs while 39-85% chymotrypsin-like activity of HGPs was insensitive to these inhibitors. The feeding of C. annum leaf extracts and two purified PIs in various doses to H. armigera larvae for two successive generations through artificial diet demonstrated their potential in inhibiting larval growth and development, delay in pupation period and dramatic reduction in fecundity and fertility. This is the first report-demonstrating efficacy of C. annum PIs against insect gut proteinases as well as larval growth and development of H. armigera. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Capsicum annum; gut proteinase; Helicoverpa armigera; insect resistance; Proteinase inhibitor

Developmental and digestive flexibilities in the midgut of a polyphagous pest, the cotton bollworm, helicoverpa armigera - Sarate, P. J.; Tamhane, V. A.; Kotkar, H. M.; Ratnakaran, N.; Susan, N.; Gupta, Vidya S.; Giri, Ashok P. (Journal of Insect Science, 2012)
Developmental patterns and survival of the cotton bollworm, Helicoverpa armigera Hubner (Lepidoptera: Noctuidae), a polyphagous insect pest, have been studied with reference to the effect of diet on major gut digestive enzymes (amylases, proteases, and lipases). Significant correlations between nutritional quality of the diet and larval and pupal mass were observed when H. armigera larvae were fed on various host plants viz. legumes (chickpea and pigeonpea), vegetables (tomato and okra), flowers (rose and marigold), and cereals (sorghum and maize). Larvae fed on diets rich in proteins and/or carbohydrates (pigeonpea, chickpea, maize, and sorghum) showed higher larval mass and developed more rapidly than larvae fed on diets with low protein and carbohydrate content (rose, marigold, okra, and tomato). Low calorific value diets like rose and marigold resulted in higher mortality (25-35%) of H. armigera. Even with highly varying development efficiency and larval/pupal survival rates, H. armigera populations feeding on different diets completed their life cycles. Digestive enzymes of H. armigera displayed variable expression levels and were found to be regulated on the basis of macromolecular composition of the diet. Post-ingestive adaptations operating at the gut level, in the form of controlled release of digestive enzymes, might be a key factor contributing to the physiological plasticity in H. armigera.
Keywords: amylases; larval performance; Lipases; Proteases

Differential protease activity augments polyphagy in helicoverpa armigera - Chikate, Yojana R.; Tamhane, V. A.; Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Insect Molecular Biology, 2013)
Helicoverpa armigera (Lepidoptera: Noctuidae) and other polyphagous agricultural pests are extending their plant host range and emerging as serious agents in restraining crop productivity. Dynamic regulation, coupled with a diversity of digestive and detoxifying enzymes, play a crucial role in the adaptation of polyphagous insects. To investigate the functional intricacy of serine proteases in the development and polyphagy of H.armigera, we profiled the expression of eight trypsin-like and four chymotrypsin-like phylogenetically diverse mRNAs from different life stages of H.armigera reared on nutritionally distinct host plants. These analyses revealed diet- and stage-specific protease expression patterns. The trypsins expressed showed structural variations, which might result in differential substrate specificity and interaction with inhibitors. Protease profiles in the presence of inhibitors and their mass spectrometric analyses revealed insight into their differential activity. These findings emphasize the differential expression of serine proteases and their consequences for digestive physiology in promoting polyphagy in H.armigera.
Keywords: adaptation; chymotrypsin; Helicoverpa armigera; polyphagy; Trypsin